2003
DOI: 10.1007/s10151-003-0020-x
|View full text |Cite
|
Sign up to set email alerts
|

Pathophysiology and prevention of loop stomal prolapse in the transverse colon

Abstract: We investigated both pathogenesis and prevention of loop transverse stomal prolapse. Seven patients with reducible prolapsed stoma were studied under fluoroscopy after staining the prolapsed stoma and the colon by barium medium while prolapsing or reducing the stoma with or without the stomal wall pressed on to the abdominal wall of fascial plane. All prolapses occurred in the distal limbs of the loop stoma with the distal transverse colons redundant. The prolapse started around the mucocutaneous suture with t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
32
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(34 citation statements)
references
References 8 publications
1
32
1
Order By: Relevance
“…Another important factor is increased intraabdominal pressure [17,18]. However, in our study, we failed to demonstrate any link with increased intraabdominal pressure, including patients with megacystis.…”
Section: Discussioncontrasting
confidence: 82%
“…Another important factor is increased intraabdominal pressure [17,18]. However, in our study, we failed to demonstrate any link with increased intraabdominal pressure, including patients with megacystis.…”
Section: Discussioncontrasting
confidence: 82%
“…Furthermore, Maeda et al [16] reported that all prolapses occurred in the distal limbs of the loop colostomy; the distal transverse colons were redundant in their study. They suggested that adding abdominal pressure to both of the prolapsing colonic walls from the serosal side induces stomal prolapse in the redundant distal colon.…”
Section: Discussionmentioning
confidence: 96%
“…Factors critical to this phenomeon include increased mobility of the transverse colon as well as shrinkage of the previously dilated distal colon, both of which have been related to an increased incidence of prolapse associated with LTC. Recently, Maeda et al [14] found that all the prolapses associated with LTC involved the distal limb. Prolapse occurs when redundant colon invades the stoma with increased abdominal pressure.…”
Section: Discussionmentioning
confidence: 99%
“…Prolapse occurs when redundant colon invades the stoma with increased abdominal pressure. Maeda et al [14] concluded that stomal prolapse might be prevented by fixation of the colon to the fascia.…”
Section: Discussionmentioning
confidence: 99%